La face de Dieu : pour une pragmatique de la spiritualité / God’s Face and the Pragmatics of Spirituality - Brînduşa Grigoriu (Anastasis: Research in Medieval Culture and Art)
In literature, God is a being endowed with a “face”: Erving Goffman’s concept (1967), reshaped by Penelope Brown and Stephen Levinson (1987), further developed by Catherine Kerbrat-Orecchioni (2001, 2005), can account for the “line of conduct” of the divine character, seen or apprehended as a person. The French and English romances belonging to the cycle of the Quest of the Holy Grail invite to the contemplation of this veiled, yet feared, face. In two hypostases : God’s “negative face”, corresponding to his territory and to his freedom from imposition, and the “positive” one, equivalent to his self-image, as delineated by relevant others (saints, angels, “celestial” knights). In its vibrant openness to humanity, the holy Grail is a literary representation of God’s “bifrons” face. It controls people’s access and departure, as well as their ontological dynamics. To illustrate this epiphany in a relevant, and explicitly religious medieval work, triggered by Chrétien’s Grail romance and going beyond the suggestions of this enigmatic paradigm, our corpus encompasses, on the one hand, the French Queste del Saint Graal of the Lancelot-Grail cycle, and, on the other hand, Le Morte Darthur, an English novel of the fifteenth century by Thomas Malory. Both texts retell, in a hermeneutic key, the accomplishment of the Quest of the Holy Grail and the assumption of Galaad. While the French text shows the hero undergo the destiny of all flesh (he falls onto his teeth), only to highlight the elevation of his soul, the English rewriting disrupts this dynamics : in this new context, Galaad’s body has no narrative existence of its own – it is only the soul that reveals itself, in meaningful ascension to heaven. All these differences play an important part in the sacred “face-work” projected by profane literature. The comparison of the French and English versions shows that the God of the Grail romances possesses specific ways of cutting a fine figure, that imply, for man, specific ways of keeping face, in a subtle interplay of cultural expectations. The theory of face-work can nurture a pragmatics of spirituality – highly relevant to the medieval corpus of the Grail Quest, in which spirits only exist to serve or apprehend the miracle of Incarnation, in a narrative knot of lights and haloes that remodel God’s self-presentation in literary life.